2012
DOI: 10.1177/1479164112440816
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of incretin during ischaemia-reperfusion

Abstract: Incretin is a gut derived peptide hormone secreted in the intestine after food ingestion, and is degraded rapidly after secretion by dipeptidyl peptidase (DPP)-4. Incretin-based therapy, such as glucagon-like peptide (GLP)-1 and the DPP-4 inhibitor, has been proposed as a new therapeutic approach for the treatment of type 2 diabetic patients. In the past few years, growing evidence also demonstrated the cardioprotective effects of incretin-based therapy, especially during ischaemia-reperfusion (I/R) injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
(146 reference statements)
2
24
0
Order By: Relevance
“…Taken together, these results suggested that geniposide pretreatment protected H9c2 cells against H/R-caused injury through Bcl-2/ Bax/mitochondria apoptotic pathways. GLP-1, a gut hormone, and GLP-1 analogs have beneficial effects on cardiovascular system by inhibiting cardiomyocyte apoptosis during I/R [23,[40][41][42][43]. It has been reported that geniposide, as a novel GLP-1R agonist, exerts different protective effects by activating GLP-1R in various tissues [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggested that geniposide pretreatment protected H9c2 cells against H/R-caused injury through Bcl-2/ Bax/mitochondria apoptotic pathways. GLP-1, a gut hormone, and GLP-1 analogs have beneficial effects on cardiovascular system by inhibiting cardiomyocyte apoptosis during I/R [23,[40][41][42][43]. It has been reported that geniposide, as a novel GLP-1R agonist, exerts different protective effects by activating GLP-1R in various tissues [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…2). Geniposide pretreatment (10,20,40, 80 μM) remarkably reduced the level of LDH (P < 0.05). LDH level in the 40 μM and 80 μM geniposide pretreatment groups were lower than that of 10 μM and 20 μM geniposide pretreatment groups (P < 0.05, Fig.…”
Section: Geniposide Decreased Ldh Level In H9c2 Cells Subjected To H/rmentioning
confidence: 99%
“…Glucagon-like peptide 1 is an incretin hormone released from intestinal L-cells that causes an increased insulin secretion, decreased glucagon secretion, and improved insulin sensitivity and has been shown to exert direct cardiovascular effects in both experimental and clinical studies with or without insulin resistance (13,14). Although the glycemic control effects of dipeptidyl peptidase-4 inhibitor have been extensively studied, the roles of vildagliptin on the heart are still unclear (15,16).…”
mentioning
confidence: 99%
“…The effects of incretin-based therapy using glucagon-like peptide-1 receptor agonists and inhibitors of dipeptidyl peptidase-4 have been promising, but need further preclinical and clinical testing [127,128].…”
Section: Reactivation Of Endogenous Cardioprotectionmentioning
confidence: 99%